2018
DOI: 10.3390/tropicalmed3020041
|View full text |Cite
|
Sign up to set email alerts
|

Improving Water, Sanitation and Hygiene Practices, and Housing Quality to Prevent Diarrhea among Under-Five Children in Nigeria

Abstract: Sub-Saharan Africa as a region accounts for the bulk of the global under-five mortality rate, to which diarrhea is major contributor. Millions of children die from diarrheal diseases each year and those who survive often do so facing suboptimal growth. Preventing the common pathways of transmission for diarrhea-causing pathogens, including improved water, sanitation, and hygiene (WASH) are regarded as the most cost-effective measures for tackling this life-threatening disease. This study aimed to quantitativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
59
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 16 publications
10
59
2
2
Order By: Relevance
“…Moreover, using water collected from unprotected (unimproved) sources for cooking/washing or for other domestic purposes was also a risk factor for childhood diarrhea in this study. This study finding is similar to studies done in northwest Ethiopia, Tamale Metropolitan Area of Ghana, South African Villages and Nigeria [32,[38][39][40].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, using water collected from unprotected (unimproved) sources for cooking/washing or for other domestic purposes was also a risk factor for childhood diarrhea in this study. This study finding is similar to studies done in northwest Ethiopia, Tamale Metropolitan Area of Ghana, South African Villages and Nigeria [32,[38][39][40].…”
Section: Discussionsupporting
confidence: 91%
“…However, other study presented that children of household with concrete roofing and walls are exposed to lower risk of diarrhea. 32 We showed no evidence between improved source of drinking water and diarrhea, consistent with the result of study conducted by Sinmegn Mihrete et al 28 However, time taken longer than 30 minutes to fetch water contributed to higher risk of diarrhea. The children who had access to fetch water within 30 minutes had no significant association with the risk of diarrhea, compared with those who can get water on premises.…”
Section: Factors Of Diarrhea Of Malawian Children Under Fivesupporting
confidence: 90%
“…The preceding study in Nigeria also indicated that unimproved toilet facility increased the odds of suffering from diarrhea. 32 With regard to the location of sanitation facility, JMP suggests that having a toilet facility on premises (within the dwelling, plot or yard) may be more important than sharing toilet facility for health. 22,37 In our study, however, toilets in own yard or plot were associated with higher risk of diarrhea in children than those who had toilets within the dwelling.…”
Section: Factors Of Diarrhea Of Malawian Children Under Fivementioning
confidence: 99%
“…26 However, it has been known that water sanitation problems increase the risk of diarrhea. 27 Access to healthy water, sanitation, hygiene interventions, and vaccination are important in avoiding and managing diarrheal diseases. 28,29 A little more than half of the babies experienced diarrhea before taken to doctor.…”
Section: Discussionmentioning
confidence: 99%